The Land between Two Seas: Art on the Move in the Mediterranean and the Black Sea 1300-1700 - Payne, Alina (Brill, 2022)
The Land Between Two Seas: Art on the Move in the Mediterranean and the Black Sea 1300-1700 focuses on the strong riverine ties that connect the seas of the Mediterranean system (from the Western Mediterranean through the Sea of Marmara, the Black Sea and the Sea of Azov) and their hinterland. Addressing the mediating role of the Balkans between East and West all the way to Poland and Lithuania, as well as this region's contribution to the larger Mediterranean artistic and cultural melting pot, this innovative volume explores ideas, artworks and stories that moved through these territories linking the cultures of Central Asia with those of western Europe.